2009
DOI: 10.1177/0886260509354881
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words: Sophomore College Men Describe Attitude and Behavior Changes Resulting From a Rape Prevention Program 2 Years After Their Participation

Abstract: The study conducted involved assessing students from a Southeastern public university during two academic years, after their participation in an all-male sexual assault peer education program. The study findings revealed that 79% of 184 college men reported attitude change, behavior change, or both. Furthermore, a multistage inductive analysis revealed that after seeing The Men's Program, men intervened to prevent rapes from happening. Participants also modified their behavior to avoid committing sexual assaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 28 publications
2
52
0
1
Order By: Relevance
“…A better choice would be to feature a heterosexual male survivor's story Running Head: MY MASCULINITY HELPS 5 first: it teaches men how it would feel to be raped, and that perpetrators are often heterosexual and use rape to control other heterosexual men (Foubert & Newberry, 2006). Depicting maleon-male rape has been shown to increase men's understanding about rape, evoke more empathy for female survivors, lower rape myth acceptance, improve bystander interventions, and reduce rape proclivity (Foubert & Newberry, 2006;Foubert & Perry, 2007;Langhinrichsen-Rohling et al, 2011;Schewe, 2002) up to 2 years post-program (e.g., Foubert, Godin, & Tatum, 2010).…”
mentioning
confidence: 99%
“…A better choice would be to feature a heterosexual male survivor's story Running Head: MY MASCULINITY HELPS 5 first: it teaches men how it would feel to be raped, and that perpetrators are often heterosexual and use rape to control other heterosexual men (Foubert & Newberry, 2006). Depicting maleon-male rape has been shown to increase men's understanding about rape, evoke more empathy for female survivors, lower rape myth acceptance, improve bystander interventions, and reduce rape proclivity (Foubert & Newberry, 2006;Foubert & Perry, 2007;Langhinrichsen-Rohling et al, 2011;Schewe, 2002) up to 2 years post-program (e.g., Foubert, Godin, & Tatum, 2010).…”
mentioning
confidence: 99%
“…Most commonly race is identified as a factor in need of further exploration as relates to sexual and gender-based violence. One sentiment that appears within the literature is that sample sizes are too small to consider racial differences and that future studies should employ larger samples (Foubert et al, 2010;Kress et al, 2006). Bradley et al (2009) justify their exclusion of race based on time constraints and note that it did not fit into the scope of their study, but they indicate a need for additional research on race as related to sexual assault prevention.…”
Section: Racial and Ethnic Identitiesmentioning
confidence: 99%
“…For example, programs geared towards risk reduction for women were found to frame women solely as survivors and/or potential survivors of sexual and genderbased violence (Breitenbecher & Gidycz, 1998;Gidycz, Lynn, Rich, Marioni, Loh, Blackwell, Stafford, Fite, & Pashdag, 2001). Similarly, among the programs examined in this review, those focused exclusively on men were found to essentialize men as sexual aggressors and/or potential perpetrators (Foubert & Newberry, 2006;Foubert et al, 2010).…”
Section: College Campus Sexual Assault Prevention Program Literaturementioning
confidence: 99%
See 2 more Smart Citations